MENINGKATKAN PEMAHAMAN TENTANG GAYA BELAJAR SISWA SMA MELALUI METODE THINK PAIR AND SHARE - Bustanul Arifin; Nora Yuniar Setyaputri; Luwi Adi Basuki (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to determine the application of classical guidance services through the use of the think pair and share (TPS) method in providing understanding and classifying the learning styles of each participant in class X-1 of SMA Negeri 2 Kediri. The methodology adopted in this study is called a quantitative approach, and to support the research, the author uses a research method with the use of numerical data that can be searched using classroom action research. Based on the implementation of the services provided, there is an increase in students' understanding of learning styles. Students who have an understanding of their learning styles are 79%, and 9 students with a percentage of 21% have a significant increase in scores related to students' understanding of learning styles. Qualification data shows that students have a visual learning style of 20 students with a percentage of 48%, followed by auditory covering 20 students with a percentage of 48% and the remaining 2 students or 4% have a kinesthetic learning style. Overall, this approach not only helps provide an understanding of students' learning styles, but also has a positive impact on students' personal development, communication skills, and social relations. Based on this, the TPS method can be used as an effective and innovative strategy to help students to provide understanding and classify student learning styles.